UiTM PBDutify: UiTM police security scheduling system / Wan Normaini Wan Mohamad Idris ... [et al.] - Wan Mohamad Idris, Wan Normaini; Shah Kamarudin, Sarah Syazwani; Salleh, Mustapha; Najmi Ayub, Suhail (2022)
The issue of security is very important in any organization, especially campuses that have many students and assets that need to be taken care of. Therefore, towards a digitalization era a system needs to be established to assist those responsible for monitoring and controlling campus security. This system will help the person in charge to organize staff schedules in a better and an orderly manner. Before this, the compilation of staff work schedules was done manually and has caused many problems to arise. One of the conflicts is when it is difficult to arrange work schedules not to overlap each other. With the existence of this system is expected to help staff to organize, update schedules and can also view the systems anytime and anywhere.